The ability of calculation average consumption of water of Daghestan rivers being absens of HMS and observation posts baising on accounting of early winter temperature variations - H. A. Ahmedrabadanova; V. Sh. Scomoya (Юг России: экология, развитие)
It was established the depending of annual average consumption of water during previos winter. The supplying of calculations with deflecting till 20% is 83-100%/